Spontaneous chromatid break as clonal evolution in myelodysplastic syndrome patients - Daniela P. Borges; Ivo Gabriel F. França; Roberta Taiane G. Oliveira; Mayara M. L. Melo; Ronald F. Pinheiro (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT Myelodysplastic syndrome (MDS) is a clonal hematopoietic stem cell disorder characterized by peripheral cytopenias due to ineffective erythropoiesis and an increased risk for evolving into acute myeloid leukemia (AML). Chromosomal abnormalities represent the most important marker of risk stratification for AML transformation. Chromatid break (chtb) is a discontinuity of a single chromatid. We report the case of a patient with MDS whose cytogenetic analysis showed spontaneous chromatid breakage (chrb): 46,XY,add(13)(q34),chtb(15)(q24) [3]/47,XY,chtb(2)(q22),del(5)(q35),del(7)(q32),+8,del(11q)(q23),del(q22)[cp17]. He was considered a high-risk patient due to the complex karyotype and the presence of chtb. We suggest that this chromosomal abnormality may be considered as a marker of genomic instability in MDS.